1958
DOI: 10.2134/agronj1958.00021962005000060013x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate Accumulation in Some Iowa Crop Plants1

Abstract: Synopsis Nitrate accumulation occurred in stalks or stems of corn, sorghum, and soybean plants. Legumes in the rotation or applications of manure or nitrogen fertilizer increased the nitrate content of the plants. The amount of nitrate in plants depended upon the stage of maturity, the degree of drouth injury, and the availability of nitrogen in the soil. Nitrate content was reduced but not destroyed by ensiling corn plants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
31
0
1

Year Published

1983
1983
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 4 publications
(6 reference statements)
7
31
0
1
Order By: Relevance
“…Consistent with these findings, the 20-cm stalk samples taken 10 cm (or lower) or 20 cm (or higher) aboveground had CSNT-N means that were more than 10% higher or lower than the CSNT obtained with the standard protocol (Table 1). These differences reflect the accumulation of nitrate in the bottom of corn stalks when N is applied in excess of crop N needs (Hanway and Englehorn, 1958;Binford et al, 1990) and support the observation that CSNTs can be used as a tool to fine-tune N fertilizer management on a field-by-field basis. The results are also consistent with data shown in Wilhelm et al (2005) that showed a difference of 15% among samples taken 10 to 30 cm, 15 to 35 cm, and 20 to 40 cm aboveground, suggesting that a change in sampling method will require a change in critical concentration.…”
Section: Statistical Analysessupporting
confidence: 68%
“…Consistent with these findings, the 20-cm stalk samples taken 10 cm (or lower) or 20 cm (or higher) aboveground had CSNT-N means that were more than 10% higher or lower than the CSNT obtained with the standard protocol (Table 1). These differences reflect the accumulation of nitrate in the bottom of corn stalks when N is applied in excess of crop N needs (Hanway and Englehorn, 1958;Binford et al, 1990) and support the observation that CSNTs can be used as a tool to fine-tune N fertilizer management on a field-by-field basis. The results are also consistent with data shown in Wilhelm et al (2005) that showed a difference of 15% among samples taken 10 to 30 cm, 15 to 35 cm, and 20 to 40 cm aboveground, suggesting that a change in sampling method will require a change in critical concentration.…”
Section: Statistical Analysessupporting
confidence: 68%
“…The basis for this test is that NO 3 -tends to accumulate in the lower portion of corn stalks under stress conditions including drought, as well as following over-application of N fertilizers and manure (Hanway and Englehorn, 1958). Post-harvest BSN measurements can potentially be useful in guiding N management in subsequent growing seasons.…”
Section: Core Ideasmentioning
confidence: 99%
“…Repr+sentation sch6matique d'une touffe d'Ammophila arenaria sur dune non fix6e (soumise aux apports de sable par le vent) avec la talle principale qui 6pie (~) et les taUes secondaires qui n'6pient pas(2,3,4,5). (~) Talle fig6e domin6e par la talle principale d'ofl l'absence d'6pis, malgr6 l'fige 6gal de ces deux talles.…”
unclassified